2000
DOI: 10.1191/096120300674499064
|View full text |Cite
|
Sign up to set email alerts
|

Activation of type I interferon system in systemic lupus erythematosus correlates with disease activity but not with antiretroviral antibodies

Abstract: The objective was to investigate the relation between serum levels of interferon-alpha (IFN-alpha), the activity of an endogenous IFN-alpha inducing factor (SLE-IIF), clinical and immunological disease activity as well as serum levels of antiretroviral antibodies in SLE. Serum levels of IFN-alpha were measured in serial sera from 30 patients sampled at different stages of disease activity (SLEDAI score). The SLE-IIF activity was measured by its ability to induce IFN-alpha production in cultures of normal perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
312
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(336 citation statements)
references
References 43 publications
17
312
2
Order By: Relevance
“…Subjects with common viral infections could still elude this screening if they do not indicate that they are ill, however these events would likely be distributed equally between controls and family members and should not result in the observed correlations. Studies have suggested that IFN-a activity varies over time in SLE patients in relation to disease activity, 3,20 however wide temporal variation in IFN-a activity in the SLE patients and their families would be more likely to obscure true familial correlations and bias toward the null hypothesis. SLE is a highly complex and heterogeneous disease that is likely caused by multiple convergent risk factors, which are different in different patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with common viral infections could still elude this screening if they do not indicate that they are ill, however these events would likely be distributed equally between controls and family members and should not result in the observed correlations. Studies have suggested that IFN-a activity varies over time in SLE patients in relation to disease activity, 3,20 however wide temporal variation in IFN-a activity in the SLE patients and their families would be more likely to obscure true familial correlations and bias toward the null hypothesis. SLE is a highly complex and heterogeneous disease that is likely caused by multiple convergent risk factors, which are different in different patients.…”
Section: Discussionmentioning
confidence: 99%
“…All SLE patients had active disease, and their mean score on the SLE Disease Activity Index (SLEDAI) (32) was 17 (range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. SLE patients had a mean C-reactive protein (CRP) level of 5.7 mg/liter, and a mean erythrocyte sedimentation rate (ESR) of 40 mm/hour.…”
Section: Methodsmentioning
confidence: 99%
“…with titers of double-stranded DNA (dsDNA) autoantibodies (11,12). Several groups have described IFN signatures in peripheral blood mononuclear cells (PBMCs), but their origin and the contribution of defined cell types remain unclear (4,10,13,14).…”
mentioning
confidence: 99%
“…It has been known for more than 25 years that patients with SLE have elevated serum IFN␣ levels (36), and that these levels correlate to both disease activity and severity (36)(37)(38). There is also a correlation between serum IFN␣ levels and several markers of immune activation typical for SLE, e.g., anti-dsDNA titers, IL-10 levels, and degree of complement activation.…”
Section: Introductionmentioning
confidence: 99%